Front Cover: Temperature‐Dependent Anharmonic Phonons in Quantum Paraelectric KTaO3 by First Principles and Machine‐Learned Force Fields (Adv. Quantum Technol. 4/2023). Issue 4 (11th April 2023) - Ranalli, Luigi; Verdi, Carla; Monacelli, Lorenzo; Kresse, Georg; Calandra, Matteo; Franchini, Cesare
Abstract : The stability of the KTaO3 quantum paraelectric perovskite at low T (ordered structure in the centre) is studied beyond the harmonic approximation for the nuclear motion, with the inclusion of the zero‐point quantum energy. Combining first‐principles methods, quantum stochastic schemes, and machine learning force fields employing local radial and angular descriptors (green and purple arcs) it is possible to asses key boson quantities like the phonon spectral function (dispersion in the background) with great accuracy and reasonable time. More details can be found in article number 2200131 by Cesare Franchini and co‐workers.